Why Not Life and Limb? Vasopressor Use in Intensive Care Unit Patients the Cause of Acute Limb Ischemia. (March 2020) - Newbury, Anastassia; Harper, Katharine D.; Trionfo, Arianna; Ramsey, Frederick V.; Thoder, Joseph J.
Background: Acute limb ischemia (ALI) of the upper extremity is a rare yet severe condition in intensive care unit (ICU) patients that generally leads to amputation. The aim of this study is to determine risk factors for development of upper extremity limb ischemia in ICU patients requiring vasopressor support.Methods: This is a retrospective study conducted from 2010 to 2015. Patients who received vasopressors during ICU admission were considered for the study. Patients were identified via Current Procedural Terminology ( CPT ) billing codes. ALI patients were matched to control patients based on diagnosis and Acute Physiology and Chronic Health Evaluation II score. Days on pressors, number of pressors, total doses, and level of ischemia were recorded. Primary end point was doses, types, and days on vasopressors. Secondary end point was level of ALI.Results: Patients in the ALI group were more likely to be started on a higher number of different types of pressors (2.6 vs 1.3 pressors). ALI patients received pressors for 8.5 days compared with 1.6 days in control patients, and received 12.8 doses compared with 3.0 doses in control patients. In addition, vasopressors with alpha-adrenergic activity were more likely to be used in the ALI group. Level of ischemia was not linked to any of the tested variables.Conclusion: Patients admitted to the ICU are more likely to sustain an acute ischemic event of an upper extremity with more vasopressor usage. Patients who received alpha-adrenergic activating vasopressors were more likely to sustain limb ischemia. When discoloration of an extremity is detected, patients should receive counteractive treatments in an effort to salvage the extremity and prevent function loss.